Pengaruh Dana Pihak Ketiga terhadap Profitabilitas Bank Perkreditan Rakyat dengan Suku Bunga sebagai Variabel Moderasi - meliza; Komala Ardiyani (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
Third-party funds are one of the important sources of funds for rural banks in Indonesia. Third-party funds are allocated to productive assets to increase profitability. Therefore, this study examines the influences of third-party funds on profitability in rural banks in Indonesia from 2019 to 2021. In addition, another factor that can also affect profitability is interest rates. Therefore, this study also examines the role of interest rates as a moderator variable. Ordinary Least Square (OLS) is employed in order to analyze the influence of third-party funds on profitability and the role of interest rates as a moderator variable.The results of the analysis show that third-party funds have a positive and significant effect on profitability. Interest rates as a moderation variable have a significant negative effect. This result shows also that interest rates have successfully moderated the relationship between third-party funds and profitability. Interest rates manage to weaken the relationship between third-party funds and profitability